Itraconazole Dosing and Drug Monitoring at a Tertiary Children's Hospital. Issue 1 (January 2019) - Leong, Ying Hua; Boast, Alison; Cranswick, Noel; Curtis, Nigel; Gwee, Amanda
Abstract : Background: Itraconazole is a broad-spectrum antifungal agent used for prophylaxis and treatment of fungal infections in immunocompromised children. Achieving the recommended target serum itraconazole trough concentration of ≥0.5 mg/L is challenging in children because of variation in itraconazole pharmacokinetics with age. We studied itraconazole use and treatment outcomes in a tertiary children's hospital. Methods: We did a 10-year retrospective review of medical records of children at the Royal Children's Hospital Melbourne who received oral itraconazole and had therapeutic drug monitoring (TDM). Results: Overall, 81 children received 92 courses of oral itraconazole and had TDM. Of 222 TDM samples, 183 (82.4%) were taken at the appropriate time (trough level at steady state). Patients ⩽12 and >12 years of age required median doses of 6.2 and 3.9 mg/kg/d, respectively, to attain target trough levels ( P < 0.001). Of children ⩽12 years of age, 71.4% required doses above the recommended dose of 5 mg/kg/d to achieve therapeutic levels, compared with 17.4% of those >12 years of age. At least 1 subtherapeutic trough concentration was reported in 63 (76.8%) courses; in only 18 (28.6%) of these was the dose adjusted. Gastrointestinal symptoms [14/92 (15.2%) courses] and hepatotoxicity [6/92 (6.5%)] were the most frequent adverse events. Neither was associated with elevated trough levels. Conclusions: The poor attainment of target levels with current recommended dosing in children <12 years of age suggests that higher empiric doses are needed in this age group. The poor compliance with TDM guidelines highlights the need for better education about appropriate timing of sampling and dose adjustment.